Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

Consecutive wet deposition of nitrogen along half of China's coastal cities induced by Super Typhoon Muifa (2022) with multiple landfalls - Ying Zhang; Baozhu Ge; Guanghua Chen; Duo Wang; Feili Li; Joshua S. Fu; Xuejun Liu; Zifa Wang (Journal of Environmental Sciences, 2025)

An Ecosystem-Based Approach to Evaluating Impacts of Fisheries Management on Ecosystem Restoration in a Chinese Subtropical Yangming Reservoir - Haibo Gong; Chengjie Yin; Jinxiang Yu; Jun Xiao; Zhijie Yu; Xuejun Fu; Bin Huang; Xiya Wu; Caigang Li (Fishes, 2025)
This study delves into the ecological implications of diverse fishery patterns on aquatic ecosystems, centering on environmental parameters, species richness, and nutrient dynamics. Using the ecological fishery management model of Yangming Lake as a case, it evaluates its influence on water quality improvement, species diversity promotion, and ecosystem stability maintenance. From 2018 to 2022, the Shannon–Wiener index in Yangming Lake increased by 17.34%, and water quality significantly improved, with phytoplankton biomass decreasing by 95.5%, total nitrogen content dropping by 33.69%, and permanganate index declining by 30.75%. Although ecological fisheries demonstrate certain effectiveness in tackling invasive species, further in-depth research is needed. This study emphasizes the importance of striking a balance between fishery development and ecological protection, in line with the United Nations Food and Agriculture Organization’s “blue transformation” strategy. Our findings offer valuable insights for sustainable fisheries development and highlight the necessity of customized management strategies to protect biodiversity and ecosystem resilience. Future research will focus on exploring the long-term ecological effects of ecological fisheries and the role of native carnivorous fish in controlling invasive species.

Hotspots of nitrogen losses from anthropogenic sources in the Huang-Huai-Hai Basin, China - Shuyu Fu; Fanlei Meng; Sijie Feng; Chenxi Yao; Jiajie Liu; Xuejun Liu; Wen Xu (Environmental Pollution, 2025)

N6-methyladenosine demethylase FTO regulates neuronal oxidative stress via YTHDC1-ATF3 axis in arsenic-induced cognitive dysfunction - Lixiao Zhou; Renjie Li; Fu Wang; Ruiqi Zhou; Yinyin Xia; Xuejun Jiang; Shuqun Cheng; Fanghong Wang; Danyang Li; Jun Zhang; Lejiao Mao; Xuemei Cai; et al. (Journal of Hazardous Materials, 2024)

Efficient recovery of vanadium from calcification roasted-acid leaching tailings enhanced by ultrasound in H2SO4-H2O2 system - Haoyu Li; Qian Ren; Jinfeng Tian; Shihong Tian; Jun Wang; Xuejun Zhu; Yuanhong Shang; Jiayuan Liu; Liping Fu (Minerals Engineering, 2024)

Effects of different ph on properties of heat-induced Auricularia auricula-judae polysaccharide-whey protein isolate composite gels - Yue Zhang; Zheng Zhang; Yuan Fu; Yawen Gao; Wanchun Guo; Ruifeng Hu; Xuejun Liu (Food Structure, 2023)

Fermentation of mead using Saccharomyces cerevisiae and Lactobacillus paracasei: Strain growth, aroma components and antioxidant capacity - Yuan Fu; Xinhua Shi; Furui Li; Xiaohui Yan; Bozheng Li; Yuan Luo; Guochuan Jiang; Xuejun Liu; Liyan Wang (Food Bioscience, 2023)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Cleaning chromium pollution in aquatic environments by bioremediation, photocatalytic remediation, electrochemical remediation and coupled remediation systems - Caiwen He; Lipeng Gu; Zhixiang Xu; Huan He; Gen Fu; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Chemistry Letters, 2020)

Extracellular production of recombinant N-glycosylated anti-VEGFR2 monobody in leaky Escherichia coli strain - Ning Ding; Xin Fu; Yao Ruan; Jing Zhu; Pingping Guo; Lichi Han; Jianing Zhang; Xuejun Hu (Biotechnology Letters, 2019)

IgG4-related inflammatory pseudotumor of the brain parenchyma: a case report and literature review - Zhuqing Zhang; Weiwei Fu; Minghui Wang; Lei Niu; Bin Liu; Yingbin Jiao; Xuejun Liu (Acta Neurologica Belgica, 2018)

A new kaurane diterpenoid from Isodon inflexus - Guang-Hua Xu; Xing-Fu Cai; Xuejun Jin; Jung Joon Lee (Natural Product Research, 2016)

Molecular characterization and expression analysis of dihydroflavonol 4-reductase (DFR) gene in Saussurea medusa - Houhua Li; Jian Qiu; Fudong Chen; Xiaofen Lv; Chunxiang Fu; Dexiu Zhao; Xuejun Hua; Qiao Zhao (Molecular Biology Reports, 2012)